Crossing Thresholds in The House of the Seven Gables: Hawthorne’s Narrative Architecture and the Encounter with History - Woodard, Luke (Nathaniel Hawthorne Review, 2025)
ABSTRACT. This article examines the formal significance of the threshold trope in The House of the Seven Gables. While readers and critics alike have long noted the threshold’s thematic importance to the story, Luke Woodard reads the architectural image as a metaphor for the novel’s narrative structure. Just as the novel’s characters are constantly stepping back and forth across the literal thresholds of the Pyncheon-house, Hawthorne employs a variety of unconventional narrative techniques to dramatize the reader’s crossing into the fictional world of his story. In doing so, Hawthorne recreates for his audience a similar process to what Clifford and Holgrave undergo over the course of the story, urging the reader to move beyond a binary conception of past and present. In the final section of the article, the author argues that the House of the Seven Gables Settlement Association and Museum in Salem currently stands as both a result and continuation of Hawthorne’s narrative technique. Woodard’s approach sheds light on the extent to which the self-reflexive formal structures of Hawthorne’s fiction are connected to his work as a writer of historical romance.
Keywords: dept.eng

Introduction: The House of the Seven Gables in Ink, Wood, and Stone - Baraw, Charles (Nathaniel Hawthorne Review, 2025)
Best-selling author Alice Hoffman’s 2023 magic-realist-bio-fiction, The Invisible Hour, features a very visible Nathaniel Hawthorne as the romantic lead. Set in the twenty-first century and in Hawthorne’s time, the story unfolds in Concord, Salem, and the Berkshires, all places Hawthorne lived. At a crucial moment in the contemporary story, the protagonist, Mia Allen, flees her abusive stepfather, who has chased her from his fundamentalist cult in the Berkshires to New York City then to Concord and to Salem—her last hope of escape. Once there, she runs directly to the House of the Seven Gables. Mia believes she might return to her beloved author, if she can reach the house where he was born. It might be another portal to the past, like “Sleepy Hollow Cemetery” in Concord, where she first traveled back in time to meet Hawthorne. Unfortunately, when she gets to the museum on Turner Street, a summer intern, “who had written a paper on The House of the Seven Gables,” has already locked the gate (Hoffman 209).1 Visiting hours are over.I start my introduction to this special issue of the Nathaniel Hawthorne Review, “The House of the Seven Gables in Ink, Wood, and Stone,” with an example from a modern prequel to The Scarlet Letter to illustrate how a central paradox about the House persists to our day: the House of the Seven Gables is real and not real. In The Invisible Hour, Mia Allen runs toward one of the most popular cultural and literary tourist sites in the United States (voted “Best Historical Home Tour” in 2025 by Newsweek magazine). When Hoffman brings Mia to Salem, she can be confident that her novel’s readers may be among the more than one hundred thousand people who visit the museum each year. This is the House of the Seven Gables as a recognizable cultural icon, a vibrant contemporary institution and an engine of economic activity in Salem’s postindustrial economy. Or rather, this is the House of the Seven Gables in “Wood” and “Stone”: a complex of antiquarian buildings, gardens, and grounds—tangible, visitable, real.Yet once Hoffman gets Mia inside the gates of the museum, a haze, fog, or something intangible descends, and she promptly disappears from the twenty-first century—becoming invisible to the hapless intern—“and nothing was as it had appeared to be” (Hoffman 209). This is the House of the Seven Gables in “Ink”—a fiction whose magic derives from the afterlife of Hawthorne’s original text. Things happen there that we might not expect in a crowded house-museum tour. Hoffman’s House of the Seven Gables becomes a literary habitation: a house as metaphor, extending across time and space. Mia, too, becomes a symbolic figure and a contemporary embodiment of the ideal reader. She makes visible our metaphors for reading as immersion and imagined presence in a world elsewhere. Her love affair with Nathaniel Hawthorne dramatizes both the contemporary popularity of romance and the history of “author love” that scholars have recognized as a powerful aspect of canon formation and literary reception.2 Hoffman’s Hawthorne—a love-object and a romantic lead, a canonical author yet still unknown, a historical person and a fictional afterlife—is himself real and unreal.An ontological ambiguity between fact and fiction has characterized the reception of the house on Turner Street in Salem since it was first called the House of the Seven Gables (now the Turner-Ingersoll House, the centerpiece of The House of the Seven Gables Museum). Within the decade following Hawthorne’s death, his readers had made the house on Turner Street, along with “The Hawthorne House” (the birthplace on Union Street) and the Custom-House, a destination for literary pilgrimages. From the start, though, this popular mode of literary reception sparked a debate about the house’s status. George Parsons Lathrop takes a side in his 1876 Study of Hawthorne, acknowledging “some slight controversy as to the original of the visionary mansion” before denying misguided attempts to locate any original (235). In his “Introductory Note” to the 1883 Riverside edition of The House of the Seven Gables, Lathrop doubles-down against the “hundreds of pilgrims annually” who visit the Turner Street house and the “delusion that there must have been a single original House of the Seven Gables, framed by flesh-and-blood carpenters” (xiii, xii). In 1880 Thomas Franklin Hunt and Henry Morrill Batchelder published the first edition of the Visitors’ Guide to Salem,3 designed to capitalize on growing tourist interest in Salem. Hunt and Batchelder agreed with Lathrop, denying the existence of the House of the Seven Gables: “Inquiries are frequently made for ‘the House of the Seven Gables,’” and “it would be very pleasant to direct admirers of the great writer to such a house, but as a matter of fact none exists or ever has existed.” Despite the evident demand, the Guide would not indulge the fantasies of literary pilgrims, who insist on a standing, tangible original of Hawthorne’s fictive house. Nevertheless, the 1880 Guide observes that “Turner street is one of the oldest in the city,” and “the stranger will not find that his time has been wasted if he takes a stroll to the old house.” The “old house,” the Guide obligingly points out, “is the last house on the right-hand side going from Derby street,” helpful directions to a House of the Seven Gables that is curiously there and not there (47).By the time Henry James visited Salem in the fall of 1904, pilgrimages by literary tourists were thriving. The Upton family had hung out a sign on Turner Street, charged admission for tours of “The House of the Seven Gables,” and sold souvenirs. Frank Cousins had produced an attractive photo-collage, “Souvenir of Hawthorne’s House of the Seven Gables,” featuring what became iconic images of “Hawthorne,” “The Birthplace,” “The Old Pump,” “The House of the Seven Gables,” and the “Grimshawe House,” and sold many others at his Essex Street shop.4But the “slight controversy” between those who came to visit the house of wood and stone and those insisting it existed only in ink and imagination continued. Text from the 1880 Guide denying the existence of the House of the Seven Gables was reproduced and expanded in several more editions. Repeating an argument from 1895, the 1902 edition of the Visitors’ Guide to Salem (advertised as the “forty-fifth thousand”) states: “‘The House of the Seven Gables’ it is useless to search for, except within the covers of the fascinating book so named” (9). This edition, the most current when James visited, also reprints a more elaborate denial from the 1895 edition, citing a description of the house in Hawthorne’s 1837 story “Peter Goldthwaite’s Treasure” as textual evidence that Hawthorne used multiple sources for the Seven Gables. The 1902 Guide claims “the frame, so to speak, of the ‘House of the Seven Gables’ seems first to have been constructed” in this early story. Though the House of the Seven Gables may not be real, literary pilgrims will find other destinations in Salem to safely identify with Hawthorne’s texts. As the Guide graciously concludes, “there are . . . so many references in [The House of the Seven Gables] to real places . . . it is not surprising the mythical is mistaken for the real by unsuspecting readers” (10).Whether delusional, “useless,” or the folly of the “unsuspecting,” it is precisely the mistaking of the “mythical” for the “real” that makes the persistence of the nineteenth- and early twentieth-century search for an original House of the Seven Gables relevant today. These literary tourist practices are reading practices, as the continuous efforts to discipline and direct them indicate. The condemnations of the “useless search” for a tangible real are consistent with early endeavors to shape Hawthorne’s reception and train readers to read him as the great “Romancer.” What critics, canon-makers, and even guidebook writers do not seem to realize is that literary pilgrimages are a form of romance, a practice that performs on the streets of Salem the blending of the “actual” and the “ideal” advocated by Hawthorne on so many different occasions. Literary tours are extratextual extensions of practices applied first to (and inspired by) the texts themselves—and often they follow protocols advocated by the very critics irritated by the tour. The unsuspecting reader seems to correspond to the vulgar tourist condemned by more discerning, culturally differentiated, “picturesque travelers” of the same period. From this perspective, the literary tourist’s reading of a place is, at the same time, a reading of the literary text.We might argue, then, that the search for an auratic, original House of the Seven Gables, in which “the mythical is mistaken for the real,” is a most Hawthornean way of reading. When Henry James finds himself “wandering perhaps astray” (The American Scene 256) after arriving in Salem, the first thing he does is to ask directions to the House of the Seven Gables, just as less-discerning tourists had been doing for several decades. Though delayed, displaced, and perhaps evaded, the search for the Seven Gables structures James’s visit—and his narrative. Even when recounting other sites and time spent elsewhere, the search returns to interrupt the narrative: first to remind us that he is still approaching the House of the Seven Gables—“to which I am coming” (258)—and later to warn us that it will all turn out to be a “dreadful anticlimax” (259). Finally, before arriving at Turner Street, James engages in a back and forth about the status of the House pointed out by his guide, the “sympathetic American boy, who dropped straight from the hard sky” (260). Even within the labyrinthine Late style, James echoes the denials Lathrop and the Visitors’ Guide repeated for twenty-five years. As James memorably puts it, when his young guide suggests the house on Turner Street is the House of the Seven Gables, “I couldn’t take it in the least” (261).There are many reasons James “couldn’t take it.” But he differs, importantly, from Lathrop and the Visitors’ Guide, which argue repeatedly against the assertion of a single original of Hawthorne’s “visionary mansion.” James does not engage that question but instead rejects any association of these wood and stone realities with the house of ink and imagination. His rejection includes those who seek to encounter the “genius” of Hawthorne in situ or the original of the House of the Seven Gables.5 As James iterates at least six times in Hawthorne, written twenty-five years before his pilgrimage to Salem, “it cannot be too often repeated that Hawthorne was not a realist” (Hawthorne 124). This central tenet of James’s influential guide to reading Hawthorne in 1879 informs his reading of The House of the Seven Gables in 1904. To put too strict an emphasis on any house or any place as the source of the real is to invite readings of Hawthorne that James is unwilling to tolerate. If direct correspondences between the house of fiction and the house on Turner Street can be so readily (and firmly) established, then “unsuspecting” literary tourists and the purveyors of literary tourism may risk mistaking the great Romancer for something much closer to the realist writers of James’s generation.James need not be too worried, though. In practice, the poetics of literary tourism welcomes the ontological uncertainty of places that have what Washington Irving calls “storied and poetical associations” (12). Literary tourists may invite what James derides as “the poor illusion of a necessity of relation between the accomplished thing [the work of art] and those other quite equivocal things [the destinations of the tour]” (The American Scene 261). But many, or most, literary pilgrims understand the “quite equivocal” nature of the sites they visit. They do not insist on the “necessity” of a fixed relation between the actual and the imaginary; on the contrary, unfixing the boundaries is the point of the tour. The “equivocal” is part of the allure.Hawthorne anticipates and even instigates all of this with the amazingly acrobatic narrative devices that start The House of the Seven Gables. From the Preface to chapter 1 and beyond, Hawthorne deliberately kicks the “ladder . . . from the top of a wall,” to borrow the closing figure of James’s Salem tour, leaving readers and tourists to “[turn] a somersault into space” and “tread the air” (The American Scene 262). Hawthorne’s house, in this novel, is there and not there on the “soil of the County of Essex” (CE 2:3), conjured, denied, ultimately entered as the visitable house of fiction: a House of the Seven Gables in ink and wood and stone. By the time Hawthorne composed these acrobatics in The House of the Seven Gables, he was already an accomplished literary tour guide. “The Old Manse” and “The Custom-House” established him as a forerunner of a proto-auto-fiction that offers both guided topographical tours (of sites that become, in the act of writing, instant tourist destinations) and visits to the author as the object of the tour. Hawthorne’s many presentations of the scene of creative production invite more intimate access to the “genius” at work than any traditional pilgrimage to an author’s birthplace, the “author’s seat,” or any other literary sites in wood and stone.Hawthorne’s innovative introductory essays, and their invocation of imagined presence, follow a long line of earlier experiments in the poetics of tourism that reach back to the unpublished collection Hawthorne once called “The Itinerant Story-teller.”6 Several tales and sketches from the 1830s and 1840s enact a tour within the story, or frame the central story with an authorial persona serving as guide—often, as in The House of the Seven Gables, to a visitable house of fiction or to sites with “storied and poetical associations.” Other texts theorize the tour. “My Visit to Niagara” (1835) performs a masterful anatomy of picturesque aesthetics, whereas the meta-fictional tour of Salem in “Alice Doane’s Appeal” dramatizes the relation of storytelling, the Gothic, and history. The Gothic tale “The Lily’s Quest” (1839) was reprinted in The Picturesque Pocket Companion, and Visitors’ Guide, Through Mount Auburn, where it helped visitors blur distinctions between fiction and the tour. Several decades later, Hawthorne’s explicit tours of Salem—“A Rill from the Town-Pump,” “Foot-prints on the Sea-shore,” “Main Street”—were transformed into a list of attractions in the Visitors’ Guide to Salem with directions to the original sites. At these sites, the Guide informs us, “one can hardly make a more pleasant pilgrimage . . . than by spending a half-hour, book in hand, reading one of his beautiful sketches, upon the very spot where Hawthorne himself stood when the inspiration seized him to write it” (Hunt, Guide 141 [1892]).This passage points again to the unresolvable paradox in the structure of literary tourism: like the two versions of the House of Seven Gables—there and not there—the “very spot where Hawthorne himself stood” is real and unreal. Literary pilgrims may walk to Essex Street or to the birthplace or to Gallows Hill, but where exactly did Hawthorne stand when “inspiration seized him”? The same writers who deny a single original structure for The House of the Seven Gables are willing to suspend skepticism about the authenticity of the real when it concerns the “very spot” where genius transpires (or possibly could). They do so because the promise of intimate relation, of imagined proximity, at the scene of creation is central to the poetics of tourism. Just as readers wish to enter and feel present in the storyworld a narrative creates, literary pilgrims wish to enter the world of the making of that story. The real becomes a means of reaching deeper into the unreal; presence on the tour intensifies the sense of presence in the text.7As the collection of essays in this special issue show, this process works in reverse as well: the fictive can enhance, or story, the real. Later editions of the Visitors’ Guide to Salem illustrate the process by closing the chapter on Hawthorne with an extract of what it calls the “weird detached paragraphs” of “Alice Doane’s Appeal.” This early hybrid text, part fiction and part sketch, certainly warrants the Guide’s description. Weird it is—formally, thematically, historically. Less expected is the praise the Guide bestows on the tale for creating a “picture of early Salem [that] is truthful and interesting” (161 [1894]). Here, the weird and Gothic point, somehow, to the real Salem. Hawthorne’s experimental storytelling “on the very spot” also spurs the people of Salem to commemorate, at last, the tragic executions on Gallows Hill. “A duty,” the Guide reports in 1894, “which the Essex Institute seeks to perform in this year of the two hundredth anniversary of the great jail delivery, the one bright spot in the gloom of that epoch in our history” (161).Whether or not that duty was performed as Hawthorne’s story envisions, “Alice Doane’s Appeal” secures a new afterlife as an incitement to both literary tourism and civic activism. In citing Hawthorne’s weird text, moreover, the Guide seems to accept the blurring of distinctions between the real and the unreal, and the imagined and the historical, that it insists on in the case of the house on Turner Street. With this appearance in the Guide, “Alice Doane’s Appeal” joins other Hawthorne texts, including The House of the Seven Gables, that have been absorbed into the de-differentiating discourse of literary tourism. After Caroline Emmerton “restored” the House of the Seven Gables in 1910 and opened the museum to the public, the process seems to have been complete. The 1916 Visitors’ Guide to Salem opens with a “Brief Itinerary” that includes: “‘House of the Seven Gables’ (so called), 54 Turner street, built about 1669; a favorite haunt of Hawthorne; now restored, with six furnished rooms, a secret staircase, furniture, relics and a ‘cent shop.’ Admission 25c” (np). . . . “This collection of houses now forms one of the greatest attractions for the visitor to Salem” (Visitors’ Guide 60 [1916]).The unusual range of materials in this special issue—a public lecture, two articles on Hawthorne’s novel, and an interview with leaders of The House of the Seven Gables Museum—presents the results of a collaboration the Nathaniel Hawthorne Society started with the museum in the fall of 2023. Members of the Hawthorne Society had long discussed initiating some form of “public humanities” project to reach across the divide between academic Hawthorne scholars, lay readers, and the vibrant institutions where the public meets Hawthorne on the ground. “The House of the Seven Gables” (and “The Old Manse” in Concord) remain popular destinations for tourists, and the people who run those sites teach tens of thousands of visitors about Hawthorne each year and help grow and sustain his readership. We wanted to join them in that work and to foster new collaborations for the future.Our first project was to establish the Hawthorne Society Annual Lecture at “The House of the Seven Gables.” Each spring, we invite a Hawthorne scholar to present a free, public lecture in Salem. Our goal is to share current scholarship with a wider public in an accessible style. We were very fortunate that the esteemed Americanist Robert Levine agreed to give our second annual lecture, which we planned to coincide with the American Literature Association conference in Boston. To complement our effort to bring an accomplished scholar to the House of the Seven Gables, we invited leaders of the museum to join us at the ALA conference. Executive Director Dakota Russell and Curator of Collections Susan Baker joined our roundtable “The House of Seven Gables in Ink, Wood, and Stone.” In keeping with our goal of taking a new approach to Hawthorne and to The House of the Seven Gables, we were pleased to invite early-career scholars to participate on the roundtable. Two were students at the time: Luke Woodard was an MA candidate and a teacher at a private secondary school and Mitchell Edwards was a PhD candidate at Rutgers. The essays and interview that follow have been expanded from the talks presented on that occasion.The Hawthorne Society Annual lecture took place Sunday afternoon after the close of conference activities. Just as we hoped members of the public would attend the lecture, we wanted to get scholars from the ALA in Boston to the House of the Seven Gables in Salem. Fortunately, a commuter ferry opened recently, and we purchased a set of group tickets, making it possible for twenty scholars from all over the world to take the trip through Boston Harbor and up the coast to Salem. The lecture took place in the “Great Chamber” of the “Hooper Hathaway House” (c. 1682), which was relocated to the museum campus in 1911 to save it from demolition. For much of the twentieth century, the house hosted Settlement classes and literary tourists in the “six furnished rooms” with baths. We had arrived, finally, at the House of Seven Gables as advertised in the Visitors’ Guide to Salem!Robert Levine gave his talk to a standing-room-only audience of students, scholars, and museum staff.8 The text of Levine’s talk, “Haunted Houses: The House of the Seven Gables and Uncle Tom’s Cabin,” is presented in this issue of Nathaniel Hawthorne Review without significant change. It strikes a fine balance between accessibility for a general audience (deftly summarizing scenes from the two haunted houses) and making an important, revisionary argument about Hawthorne’s engagement with questions of race and slavery in The House of the Seven Gables. Levine shows how the numerous references to color, blood, and race in the novel complicate and undermine the notions of white, racial purity that underlay Colonel Pyncheon’s “genealogical ambition to perpetuate his supposedly white family.” Thus, the original house of Pyncheon is haunted by more than Maule’s curse. Levine’s lecture, informed by his forthcoming book on Stowe and Black America, closes with a review of some interesting biographical convergences between the authors of the two houses that should serve as a corrective for our partial accounts of Stowe’s anger with Hawthorne’s dedication of Our Old Home to Franklin Pierce (“that traitor”!). Levine points out that despite her earlier outrage, Stowe gave her daughter an elegantly bound edition of Hawthorne’s collected works in 1865.The two essays that follow Levine’s “Haunted Houses” move comfortably back and forth between elements of the House’s unstable ontological status that I have outlined in this introduction: Hawthorne’s fictional narrative, the House of the Seven Gables in ink, and the novel’s afterlife as The House of the Seven Gables Museum in wood and stone. They conduct close, formal analyses of the narrative structures Hawthorne builds in his “visionary house,” and, as a nimble literary tourist might do, they read the history of the house through the lens of—and as an interpretation of—Hawthorne’s novel. The unreal and the real are in full dialectical play in both essays. Crucially, each moves beyond the binary of ink and wood to consider the House of the Seven Gables in the world—as it figures in the history of novelistic technique and on the “soil of the County of Essex” (3) and in the history of American literary criticism. Together they present new perspectives on the House of the Seven Gables in ink, wood, and stone as it persists in the wider literary and physical worlds.Luke Woodard’s “Crossing Thresholds in The House of the Seven Gables: Hawthorne’s Narrative Architecture and the Encounter with History” (this issue) begins by directing our attention to the interventions of Hawthorne’s narrator and to Hawthorne’s narrative technique in The House of the Seven Gables. Woodard shows that the trope of the threshold, often considered in terms of characterization and theme, also represents Hawthorne’s work as a “narrative architect . . . who constructs a house of words . . . that will be inhabited by readers.” Hawthorne’s house of ink, in Woodard’s conception, contains the house of stone within the fictional storyworld. Woodard takes the manifest threshold crossings as a trope for the way Hawthorne persistently blurs the very distinctions he claims to maintain between the real and the imaginary and the past and the present. He argues that Hawthorne uses this liminal “narrative architecture” along with the scenes of storytelling inside The House of the Seven Gables to dramatize “the importance of form and style in facilitating an imaginative encounter with history.” In a final critical turn, Woodard looks ahead to Hawthorne’s influence on The House of the Seven Gables Museum as evidence that “Hawthorne’s narrative techniques have achieved physical expression . . . [in] a real structure.” The House of the Seven Gables in ink and wood crosses the threshold into the historical, contingent world.Mitchell Edwards’s “Flip This House: Caroline Emmerton’s Activist Hermeneutics and The House of the Seven Gables” takes this turn to the House of the Seven Gables in the world even further. He uses archival research, book history, and an original conception of activist literary criticism to historicize Caroline Emmerton’s work at the House of the Seven Gables and “flip” our understanding of her contributions. Edwards starts with the assertion that “the house and the book are two linked components of a composite cultural text” and argues that Emmerton’s renovations of the House also begin her renovation of Hawthorne’s novel, or, more precisely of the visitor-reader’s interpretation of the book. Edwards further shows that Emmerton’s varied activities, her essays, plays written for performance at the Settlement house, and republication of the “Visitors’ Edition” of the novel constitute a form of social activism and literary interpretation—what he calls an “activist hermeneutics.” Edwards reads Emmerton’s contribution to this emerging mode in the context of other twentieth-century activist literary movements and concludes with the bold claim that Emmerton is “invested in conscripting Hawthorne for radical social change, placing him at the center of a public humanities project marked by its Progressive Era origins.”Those origins continue to influence how visitors experience the House of the Seven Gables and to inform the larger work of the “House of the Seven Gables Settlement Association” (Emmerton’s original organization, which owns and operates the museum). We close this special issue with an edited transcript of an interview with our partners in our contemporary public humanities project: Executive Director Dakota Russell and Curator of Collections of the Seven Gables Susan Baker. Russell and Baker talk about the history of the House since Caroline Emmerton created the Settlement Association and opened the museum, about continuities with Emmerton’s mission in their settlement work and programming today, and about their representation of Hawthorne’s work and life at the Seven Gables. They also discuss their new initiative to revitalize the Hawthorne birthplace museum and to become a hub for Hawthorne studies and literary tourism. The Hawthorne Society has collaborated on this project from its inception, and we will continue as it goes forward. (You may hear more about fundraising efforts in the future.)We hope to see you in Salem for our next House of the Seven Gables lecture—and then again in June of 2028 for our next international Hawthorne Society conference!
Keywords: dept.eng

The House of the Seven Gables Then and Now: A Conversation with Executive Director Dakota Russell and Curator of Collections Susan Baker of The House of the Seven Gables Settlement Association (transcript from September 18, 2025) - Baraw, Charles; Russell, Dakota; Baker, Susan (Nathaniel Hawthorne Review, 2025)
ABSTRACT. A conversation with Dakota Russell, Executive Director, Susan Baker, Curator of Collections from The House of the Seven Gables Settlement Association, and Charles Baraw, past president of the Nathaniel Hawthorne Society.
Keywords: dept.eng

Thematic section on premodern digital ecologies - Malcolm, Aylin; Richmond, Andrew (Digital Scholarship in the Humanities, 2026)
Keywords: dept.eng

Property and precarisation: reading Seth Tobocman’s War in the Neighborhood and Fly’s CHRON!IC!RIOTS!PA!SM! - Stretch, Cynthia (Textual Practice, 2025)
Keywords: Fly (Elen Orr); Isabell Lorey; Property (philosophy); Reading (process); Seth Tobocman; bad debt; dept.eng; precarisation; squatting

Making the Radical University: Identity and Politics on the American College Campus, 1966–1991 - Kalbfleisch, Elizabeth M. (University of Massachusetts Press, 2024)
In the 1960s, professors, students, and activists on the political Left viewed college curricula as useful sites for political transformation. They coordinated efforts to alter general education requirements at the college level to foster change in American thought, with greater openness toward people who had previously been excluded, including women, people of color, the poor and working classes, people with disabilities, and members of the LGBTQ community. Their work reshaped American culture and politics, while prompting a significant backlash from conservatives attempting to, in their view, protect classical education from modern encroachment. Elizabeth M. Kalbfleisch details how American universities became a battleground for identity politics from the 1960s through the 1980s. Focusing on two case studies at Stanford University and the University of Texas at Austin, Making the Radical University examines how curricular changes led to polarizing discussions nationwide around academic standards and identity politics, including the so-called canon wars. Today, these debates have only become more politically charged, complex, and barbed.
Keywords: dept.eng

Christian identity, piety, and politics in early modern England - Dodson, J. Michael (Reformation, 2023)
Keywords: book.review; dept.eng

Virginia Woolf, money, and “the world’s oldest profession” - Neverow, Vara (ITINERÁRIOS – Revista de Literatura, 2023)
Keywords: dept.eng

Oh So Yum! Inspiring Others to Explore the Many Flavors of Plant-Based Nutrition with Everyday Favorites and Weekend Fun Food: Volume 1: Non-Dairy Edition - Gibson, Lori Angelica (White Dove Cottage Industries, LLC, 2023)
Oh So Yum! Volume 1 is a little bit gourmet and a little bit every day. With recipes for non-dairy cheeses, savory entrees, sweet treats and so much more, there is something to satisfy every craving and the most discriminating palates.Whether you're new to plant-based nutrition or a seasoned veteran, you can continue to enjoy your favorite flavors while benefitting animals, the planet and your health. This book will show you how and will quickly become your most reached for resource for quick and easy, tasty and satisfying, crowd-pleasing meals.Praise for Oh So Yum!“Oh So Yum is not just the title of this wonderful book. It is exactly what this book is about—creating delicious and surprisingly easy foods that have all the taste and none of the regrets that often accompany tasty meals. The instructions are simple, and the results are spectacular.” - Neal D. Barnard, MD, FACCAdjunct Professor, George Washington University School of MedicinePresident, Physicians Committee for Responsible Medicine“Anyone who thinks plant-based eating means sacrificing foods you love, this book will quickly change your mind! Written from a clear place of passion—Lori has created the ultimate introduction and delicious guide full of many classic dishes and favorite desserts, plus lots of staple recipes to keep stocked in your fridge and use a thousand different ways!”- Natalie ThomasRecipe and Video Creator, Feasting on Fruit“Lori’s Feta cheese is FANTASTIC!!! She could start up a business selling vegan cheeses. I bet there are a lot of people looking for good alternatives – this one is the best!- Dawn Duval, Area Supervisor“Wow! Lori’s aged blue cheese is delicious. I was going to let it sit in the cellar to age a bit longer but couldn’t resist trying it with some marinated eggplant!!! Thank you again!!!!!!”- Cindy Schrank Kane, Maven of Moderation“The ricotta recipe turned out great! Very easy. I usually make a cashew ricotta but will be replacing it with this recipe because this tastes a lot more like real ricotta to me. I bet I could swap this for dairy ricotta in any stuffed/layered pasta recipe without my non-veg friends and family noticing. I made the red pepper-fennel pasta with it too and liked how easy it was to transform the ricotta into a creamy pasta sauce.”- Melissa McBerkowitz, Recipe Testing Team, USA“The gelato is absolutely delicious! I took a portion to my mother who is vegetarian and trying to reduce her dairy intake and she said if she could buy vegan ice cream like this in the shops she would be very happy!”- Caroline Christian, Recipe Testing Team, UKWhat’s inside: 50+ whole food plant-based recipes including…Fresh, cultured and aged cheeses including feta, ricotta, mozzarella and cream cheese, plus REAL aged cheeses such as Camembert and Blue cheese.Veganized versions of popular dishes including stuffed shells, spanakopita (Greek Spinach Pie) and zucchini pad Thai.Dressings, sauces, appetizers and sides such as gourmet blue cheese dressing, marinated feta, mushroom antipasto, marinated eggplant and even potato salad.Weekend fun foods including smoked portobello CrunchWrap, jackfruit caritas and pizzeria style pizza.Fabulous desserts such as cheesecake, cashew cream parfaits, chocolate peanut butter pie and gelato.
Keywords: dept.eng

"A Charnel House of Uncertainty, Doubt, and Error": Medical and Narrative Authority in Some Fin-de-Siècle Fictions - Fluhr, Nicole (Literature and Medicine, 2021)
Keywords: dept.eng; peer-reviewed

“Maybe There’s Nobody to Shoot”: The Disappearing Landlord in 20th-Century U.S. Fiction - Stretch, Cynthia (American Houses: Literary Spaces of Resistance and Desire, 2022)
Keywords: American Studies; General; History; North America; Social Sciences; dept.eng

At Home on the Stage: Toward an Affective Geography of Gentrification and Eviction in U.S. Cities - Stretch, Cynthia (Literary Representations of Precarious Work, 1840 to the Present, 2021)
Spoken word performance addressing gentrification and eviction encodes and embodies increasingly abstract and bureaucratically obfuscated processes of racialized dispossession in U.S. cities. Developing tropes across three works about housing precarity are read as poets’ attempts to identify the antagonists behind the digital wall of finance capital. Whereas the interactions of housing-insecure people with and within the housing market generate socially devalued identities, spoken word’s emphasis on “authenticity” requires poets to stand up as and for themselves as they wish to be (seen). In so doing, poets attempt to connect with audiences in real time to locate or reconstitute a stance as agents, however provisionally.
Keywords: A Scribe Called Quess?; Eviction; Gentrification; Nick Petrie; Roya Marsh; Spoken word poetry; dept.eng

War in Travel Literature - Dubino, Jeanne; Kocabıyık, Orkun; Marino, Elisabetta; Smyth, Andrew J. (Cambridge Scholars Publishing, 2023)
These twelve chapters show how war functions as a subject, theme, impetus--willing and not--and backdrop in travel writing. Literature about travel and war in tandem enables readers to rethink both categories. The forms of travel writing about war addressed in this collection, including cookbooks and military magazines along with nonfiction narrative and memoir, reveal how heterogenous travel writing can be. To study travel in connection with war expands readers' understanding of the multiple motivations instigating travellers' journeys. War is about more than fighting on a battlefield; its reach is extensive, encompassing the spheres surrounding its battlefields and fronts. The many actors involved in any conflict attests to the ways war is absorbed into their worlds, permeates their thoughts and spurs their actions. Readers interested in travel literature from the beginning of the nineteenth century through the present day will find this volume to be of especial interest.
Keywords: dept.eng

Chronic: A Memoir - Dimyan, Rebecca (Woodhall Press, 2023)
In this powerful debut, Rebecca Dimyan details her experience with endometriosis, a chronic disease which effects one in ten women worldwide. This painful condition takes an average of seven years to be diagnosed and has no proven cure. Most women will undergo multiple surgeries, take countless painkillers and other drugs, and will still endure regular pain and other complications. With honesty, vulnerability, and sometimes humor, Dimyan explores the ways the condition has impacted her experiences, her body, her pain, and her joy. She takes her audience on an emotional journey through her teenage years, early twenties, and into her thirties as she becomes a professional woman, wife, and mother. Dimyan blends research, anecdotes, and advice as she shares the relief she’s found through alternative treatments and holistic medicine. Chronic isn’t just a story about one woman’s illness—it is a memoir about all the pain, pleasure, heartbreak, friendship, love, and hope she experiences on her path to healing.
Keywords: dept.eng

Lessons for My Daughters (Taught to Me by bell) - Hutchinson, Brandon L. A. (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
As a tenured professor at a predominantly white institution (PWI), I am aware of the hardships we face in the academy; as a mother of three Black girls, a wife to a Black man, I am full. And yet, I must make space to see my own self clearly. Each day as a Black woman, I must set the intention to save my own life.
Keywords: Identity; Introspection; Self-care; dept.eng

My Face-Eating Octopus - Furey, Rachel (Harpur Palate, 2023)
Keywords: dept.eng; literary-nonfiction

The Life and Times of Chinua Achebe - Ogbaa, Kalu (Global Africa, 2022)
"The Life and Times of Chinua Achebe introduces readers to the life, literary works, and times of arguably the most widely-read African novelist of recent times, an icon, both in continental Africa and abroad. The book weaves together the story of Chinua Achebe, a young Igboman whose novel Things Fall Apart opened the eyes of the world to a more realistic image of Africa, a continent warped by generations of European travelers, colonists, and writers. Whilst continuing to write further influential novels and essays, Achebe also taught other African writers to use their skills to help their national leaders to fight for their freedoms in the post-colonial era, as internal warfare compounded the damage caused by European powers during the colonial era. In this book Kalu Ogbaa, an esteemed expert on Achebe and his works, draws on extensive research and personal interviews with the great man and his colleagues and friends, to tell the story of Achebe and his work. This intimate and powerful new biography will be essential reading for students and scholars of Chinua Achebe, and to anyone with an interest in the literature and post-colonial politics of Africa"--
Keywords: 20th century; Achebe, Chinua; Achebe, Chinua; Biography; Political and social views; Authors, Nigerian; dept.eng; faculty_collection

Poisoning the Wells: Antisemitism in Contemporary America - Pessin, Andrew; Blackmer, Corinne E. (ISGAP, 2021)
Keywords: Antisemitism; United States; dept.eng; faculty_collection

Should we teach students how to bullshit? - McEachern, Peter J.; McEachern, Robert W. (Writing and Pedagogy, 2022)
Bullshit, as defined by Frankfurt (2005, p. 10), is language that is “disconnected from a concern for the truth.” Much scholarship shows that bullshit is a prominent feature in organizations that is difficult, if not impossible, to get rid of (e.g., McCarthy et al., 2020; Penny, 2010). Bullshit, by definition and by cultural practice, seems antithetical to business writing orthodoxy. As Thill and Bovée (2020) suggest in a representative textbook, communication should be clear and ethical. However, Spicer (2020) codifies bullshit as a social practice whose outcomes are not always dire. Well-crafted bullshit benefits its users, allowing them to “fit into a speech community, get things done in day-to-day interaction and bolster their image and identity” (Spicer, 2020, p. 20). Contrasting with business writing’s abstinence-only bullshit stance, this suggests that successful writers must adapt to their organization’s speech act practices. In this article, we argue that students must be taught about bullshit. After describing bullshit and its role in organizations, we show how business writing could incorporate a critically informed approach to bullshit in undergraduate courses, internship preparation courses, and other curricular instances in which students work directly with organizations. While bullshitting should not be outright encouraged, continued ignorance will do nothing to solve its associated problems. Promoting bullshit literacy, however, could both minimize bullshit’s harms and maximize its benefits. We close by describing how this approach could foster critical thinking skills, promote more seamless adaptation to organizational cultures and communication practices, and perhaps even improve mental health outcomes.
Keywords: Bullshit; Bullshitology; Business Writing; dept.eng; peer-reviewed

We Need to Talk About War Metaphors in Oncology - McEachern, Robert W. (JCO Oncology Practice, 2022)
Keywords: dept.eng

Tea Ceremony - Sonnenschein, Dana (Corvid Queen, 2022)
Water the color of oolong reflects her shape vanishing.
Keywords: dept.eng; ⛔ No DOI found

Nest Robbers - Sonnenschein, Dana (The Curator, 2022)
...
Keywords: dept.eng

Queering Anti-Zionism: Academic Freedom, LGBTQ Intellectuals, and Israel/Palestine Campus Activism - Blackmer, Corinne E. (Wayne State University Press, 2022)
"This book explores the work of five influential pro-BDS (Boycott, Divestment, and Sanctions) queer academic activists-Sarah Schulman, Jasbir Puar, Angela Davis, Dean Spade, and Judith Butler-each of whom exemplify different ideological and critical practices around anti-Zionism"--
Keywords: Boycotts; Foreign public opinion; Israel; Boycott, divestment, and sanctions movement; Zionism; Gay rights; Israel; Israel; Disinvestment; Politics and government; dept.eng; faculty_collection

Bird Guides (poem) - Sonnenschein, Dana (Thimble Literary Magazine, 2022)
Keywords: dept.eng

Lady Macbeth, her book - Sonnenschein, Dana (Embark: A Literary Journal for Novelists, 2022)
A.D. 1034 The king and queen took hawks out that day, and their retinue trailed along hills and swales, watching as Duncan and then Suthen lifted gauntleted arms and opened their fists. The hunting…
Keywords: dept.eng; ⛔ No DOI found

The life and times of chinua achebe - Ogbaa, K. (2021)
The Life and Times of Chinua Achebe introduces readers to the life, literary works, and times of arguably the most widely-read African novelist of recent times, an icon, both in continental Africa and abroad. The book weaves together the story of Chinua Achebe, a young Igboman whose novel Things Fall Apart opened the eyes of the world to a more realistic image of Africa that was warped by generations of European travelers, colonists, and writers. Whilst continuing to write further influential novels and essays, Achebe also taught other African writers to use their skills to help their national leaders to fight for their freedoms in the post-colonial era, as internal warfare compounded the damage caused by European powers during the colonial era. In this book Kalu Ogbaa, an esteemed expert on Achebe and his works, draws on extensive research and personal interviews with the great man and his colleagues and friends, to tell the story of Achebe and his work. This intimate and powerful new biography will be essential reading for students and scholars of Chinua Achebe, and to anyone with an interest in the literature and post-colonial politics of Africa. © 2022 Kalu Ogbaa.
Keywords: dept.eng

Landscape in Middle English Romance: The Medieval Imagination and the Natural World - Richmond, Andrew M. (Cambridge studies in medieval literature, 2021)
"In Sir Isumbras, one of the most enduringly popular late medieval romances, the penitential experience of its eponymous hero (modeled off of the evergreen St. Eustace tales) is grounded in a careful exploration of hillside ironmines and the communities of smiths that rely upon them. Such an interest in natural resource management and industrial development derives from the notable focus on charting topography that distinguishes the central third of the romance - marking Isumbras's transition from secular to divine systems of values, and his geographical movement from Christian to Saracen lands. Similarly, in the fourteenth-century Middle English version of William of Palerne (hereafter William), the eponymous protagonist flees with his lover, Melior, through a world of forests and bays that overflows with topographical details. These intricate explanations of quarry pits, hollow oaks, roadside groves, seaside caves, and war-torn estates together compose a perspective on landscape defined by networks of economic exchange. In this regard, the predominant view of the natural world presented in William ties it to earlier romances such as Havelok the Dane, a text interested in the systems of exchange that knit seaside fishermen to urban markets; and to later texts such as the Middle English versions of Partonope of Blois, which demonstrates in its depictions of estates the mercantile and agricultural uses of natural spaces that underlie the successful maintenance of a noble identity. This chapter, then, will discuss how Middle English romances' attention to the management and harvest of natural resources often reveals the link between country and urban spaces created by the exchange of such goods. I will also consider how sympathetic portrayals of laborers and other low-class harvesters of natural resources suggest that romances, particularly around the turn of the fifteenth century, reflect the shifting nature of their bourgeois-gentry audience by engaging with the environmental experiences of merchants, household clerks, reeves, franklins, and gentry farmers in addition to those of the higher aristocracy"--
Keywords: History and criticism; English literature; History and criticism; Landscapes in literature; Seashore in literature; Middle English, 1100-1500; Romances, English; SCSU Faculty Scholar Award; award_winner; dept.eng

Lord of the Forest | Good Fences - Sonnenschein, Dana (Kosmos Journal, 2021)
Keywords: dept.eng; peer-reviewed; ⛔ No DOI found

Meeting the Dire Wolf – Dana Sonnenschein - Sonnenschein, Dana (panoply, a literary zine, 2021)
Not just heavy bones. The huge skull fleshed, broad across the brow and muzzle, 3” canines, thick neck and body — the wolf of your nightmares and not just one.  Thirty. A pack drawn to the sce…
Keywords: dept.eng

Winter's Orphan - Sonnenschein, Dana (O:JA&L (Open: Journal of Arts & Letters), 2021)
Keywords: dept.eng; ⛔ No DOI found

Empirical insights into college students’ academic reading comprehension in the united states - Kalbfleisch, Elizabeth; Schmitt, Elena; Zipoli, Richard P. (Journal of College Reading and Learning, 2021)
This article reports on a collaborative research project involving faculty in writing studies, communication disorders, and applied linguistics that sought to empirically describe the reading skills of students (N = 910) in freshman composition classes at one college and two universities in the northeast United States. The research team developed and administered a questionnaire that evaluated students’ reading abilities according to six categories: inferential ability, background knowledge, general comprehension, vocabulary, figurative language/jargon, and morphosyntactic structures (grammar/syntax). Our statistically significant results showed that students scored best in the categories of background knowledge and general comprehension, which are well researched in a college population. However, students struggled in categories such as figurative language/jargon and morpho-syntactic structures, which are not well researched in a college population. Further, comprehension seemed generally discrete (understanding specific points of an essay) rather than holistic (indicated by an ability synthesize those points into a general statement about the author’s thesis). These findings suggest that further empirical research in this area will help describe the reading skills of college students and consequently will inform the development of pedagogical approaches that more effectively address students’ current needs. © 2021 College Reading and Learning Association.
Keywords: dept.cmd; dept.eng; dept.wll; peer-reviewed

Mistress of Snow - Sonnenschein, Dana (Gingerbread House Literary Magazine, 2021)
Hinges creak, and she swirls in the door, puts her finger to blue lips. Cold takes the old woodcutter, eyes open, breath frozen in his beard.  But crystals melt in your lashes as you gaze on her gl…
Keywords: dept.eng

Becoming allies accomplices: Problematizing the intersection of reflection and action through pre-service teachers’ autoethnographies as praxis - Sinclair, Meredith N; Powell, Jessica S (International Journal of Critical Pedagogy, 2020)
This paper explores the phenomenon of pre-service teachers becoming accomplices for racial justice. Using hermeneutic phenomenology, we examine the experiences of three white, female pre-service teachers navigating this terrain. A framework we are naming autoethnography as praxis emerged from this inquiry. Our research interrogates the notion of white allies and the intersection of critical dialogue and action in pre-service teacher education. Building off of perspectives in critical race and critical whiteness studies, this work is grounded in the reality of the material permanence of white supremacy that white teachers must acknowledge and develop tools to dismantle. Autoethnography as praxis moves students from simply analyzing and reporting their experiences (including their emerging understanding of white privilege) through autoethnography to examining how their experiences have shaped and will continue to shape their identities and practices as teachers. By reframing autoethnography as a dialogue between researcher and her texts, we hope to push beyond reflection to action. By engaging participants in reflection on their actions, autoethnography as praxis also addresses the flaw of white teachers acting as benevolent allies who set their own agenda and position people of color as “needing their assistance.” © 2020, University of North Carolina at Greensboro. All rights reserved.
Keywords: Anti-racist pedagogy; Praxis; Social justice; Teacher education; Whiteness; dept.cur; dept.eng; peer-reviewed; ⛔ No DOI found

Mary Johnson of Wethersfield, Connecticut, hanged for witchcraft, 1648 (poem) - Shipley, Vivian (Connecticut Literary Anthology: Celebrating Nutmeg Authors, 2020, 2020)
Connecticut Literary Anthology features thirty-six Connecticut poets and prose writers from across the Nutmeg State. The 2020 Anthology is published by the Central Connecticut State University English Department. The writers in the inaugural anthology share themes amplified by current events, but not the context. Stories of family, economic in- equality, sexual violence, social justice, culture wars, lost love, aging, and gender—they’re all in here. And mangoes. Everyone loves mangoes. Featured writers: Janet L. Bannister, Charles V. Belson, Susan Cinoman, Ginny Lowe Connors, Jason Courtmanche, Catherine DeNunzio, Joanie DiMartino, Catherine DeNunzio, Meghan Evans, Maura Faulise, Kathryn Fitzpatrick, Beth Gibbs, Cecilia Gigliotti, Nichole Gleisner, Sitara Gnanaguru, Emi Gonzalez, José B. González, Benjamin S. Grossberg, Avery Jenkins, B. Fulton Jennes, Sarah Darer Littman, Kiran Masroor, Melissa McEwen, Claudia McGhee, Nancy McMillan, Jean P. Moore, Steven Ostrowski, Makenzie Ozycz, Aimee Pozorski, Kara Molway Russell, Vivian Shipley, Amy Sisson, Katherine A. Szpekman, Wendy Terry, Mika Taylor, Marina Tinone, Jason Wilkins. Praise for Anthology: "It feels like we have become unglued from one another since March of 2020; masked strangers passing each other in anonymity. But this anthology glues us back together and helps us find ways to heal and talk with one another. Important stories are told, and we should heed them." —Lisa Comstock, Director for Connecticut Center for the Book
Keywords: dept.eng

Maps for Jackie - Labbe, Jason (BlazeVOX Books, 2020)
"Poetry's natural habitat is one of detail, radiant or tarnished, an intimate geography that draws us close to where presence is an act of perception: world into word. In Maps for Jackie, Jason Labbe navigates a terrain of singular encounters and incidents, tactile, luminous and animated by the sensuous abrasions and comforts of the heartmind as they touch down on his, and our, present: white leaf is like a moth / wing I'd fix to her shoulder.--Ann Lauterbach"--The back cover
Keywords: 21st century; American poetry; dept.eng; faculty_collection

Michelangelo's Captive - Sonnenschein, Dana (The Ekphrastic Review, 2020)
Michangelo’s Captive  ​ I wished to photograph a beautiful man sculpted by Michelangelo, afraid I would forget him if I did not, for he had no story, no name.  But I turned away.  I had the...
Keywords: dept.eng; ⛔ No DOI found

Utility, artistry, and narrative control in Herman Melville's "The Bell-Tower" - Ellis, Scott (College Literature, 2020)
Keywords: dept.eng; peer-reviewed

"Train & Pool," “The Colonel Takes a Position," "Summer Almanac," "Cloud Study," "Light, A Reagent," Author's Statement: "Writing, For and To" - Johnson, Brian (Parhelion, 2020)
Keywords: dept.eng; ⛔ No DOI found

"Asides" and "Household" - Johnson, Brian (Court Green, 2020)
Keywords: dept.eng; ⛔ No DOI found

Maple Street, London (1915) - Johnson, Brian (The Ekphrastic Review, 2020)
Keywords: dept.eng; ⛔ No DOI found

Rhubarb Leaf - Johnson, Brian (great weather for MEDIA, 2020)
Keywords: dept.eng; peer-reviewed; ⛔ No DOI found

Tour - Johnson, Brian (The Main Street Rag, 2020)
Keywords: dept.eng; ⛔ No DOI found

W. D. Howells, William James, and the pragmatist pluralism of “The Angel of the Lord” - Petrie, Paul (American Literary Realism, 2020)
Keywords: dept.eng

Unsettling transcription through “event memory”: problem and possibility in exploring the phenomenological question - Sinclair, Meredith N. (Qualitative Inquiry, 2020)
This article works to unsettle the use of transcription in qualitative inquiry by troubling the truth claims of transcribed text. Building on the hermeneutic phenomenology of Van Manen, it explores the way the researcher might “write through” transcribed text to return to the two-dimensional text space a more honest reading of lived experience. It also draws on Deleuze and Guattari’s rhizomatic thinking to explore the “gruesome multiplicities” present in reality—and the ways we might honor that multiplicity in research texts. Excerpts from an inquiry into the phenomenon of “reading as not a reader” are used to illustrate.
Keywords: dept.eng; hermeneutic phenomenology; methodologies; methods of inquiry; peer-reviewed; qualitative research; qualitative research and education; transcription; writing as method of inquiry